Pengaruh Metode Latihan High-Intensity Interval Training (Tabata) terhadap Peningkatan VO2max Atlet Handball Jawa Tengah - Faizal Shauma; Muhlisin Muhlisin; RR Noer Indah Aprianti; Yudhi Purnama; Rian Kurniawan; Dian Listyarini (Universitas Negeri Surabaya, 2024)
Background: This study aimed to measure the effect of High-Intensity Interval Training (HIIT) with the Tabata protocol on increasing Volume Oxygen Maximum (VO2max) in Central Java handball athletes. The main problem faced is the need for handball athletes to have optimal physical endurance and cardiovascular fitness to support performance during matches. The conclusion of this study is that the HIIT (Tabata) training method has a significant effect on increasing VO2max and can be implemented in handball athlete training programs to improve physical fitness and athlete performance on the field. Methods: The method used was an experiment with a one-group pretest-posttest design, involving 14 Central Java handball athletes selected using the Saturation Sampling technique. The data collection instrument was the Multistage Fitness Test (Beep Test), which was conducted before and after an 8-week intervention period. Data analysis was performed using the Shapiro-Wilk normality test and the paired sample t-test hypothesis test using SPSS version 17. Results: The results showed a significant increase in VO2max in handball athletes after being given HIIT training with the Tabata protocol, with an average increase of 8.8% from pretest to posttest. Conclusions: The conclusion of this study is that the HIIT (Tabata) training method has a significant effect on increasing VO2max and can be implemented in handball athlete training programs to improve physical fitness and athlete performance on the field.